The Least Developed Countries Report 2014 - United Nations Conference on Trade; Development (United Nations, 2014)
As we reach the target date to meet the Millennium Development Goals (MDGs), the LDC Report analyses the performance of the LDCs in progressing towards these goals and provides a framework for their development policies in the post-2015 period. The Report shows that there is a high degree of differentiation among LDCs’ performance towards the MDGs, but most of these countries will not be able to attain most MDGs. This disappointing outcome is surprising given that LDCs have experienced historically high economic growth rates over the last 20 years, and domestic and international policies for LDCs have set MDGs as top priority. In the coming post-2015 period, the LDCs will face the challenge of achieving the sustainable development goals (SDGs), for which structural transformation will be a precondition.